Collective Argumentation through Scaffolding: Homogeneous and Heterogeneous Groups in Solving Mathematics Tasks - Ekawati, Aminah; Siswono, Tatag Yuli Eko; Lukito, Agung (Mathematics Education Journal, 2025)
Collective argumentation plays a crucial role in enhancing students' mathematical understanding through discussion. While previous studies have explored collective argumentation and group composition, only a limited number of research has examined the impact of ability-based grouping—both homogeneous and heterogeneous—on collective argumentation in mathematics learning. Based on this, the current research aims to explore collective argumentation in homogeneous and heterogeneous groups of students, supported by scaffolding, in solving mathematically and non-mathematically rich tasks. Using a qualitative approach with a case study design, the present study involved two groups of eighth-grade students, each consisting of six eighth-grade students with high, medium, and low abilities. Data were collected through recorded group discussions, observations, and interviews. After that, the collected data were analyzed using the Toulmin argumentation model. The findings reveal that homogeneous groups of high-ability students engaged more actively in idea exploration and generated dynamic arguments, incorporating key argumentation elements such as claims, data, warrants, rebuttals, and qualifications. In contrast, in heterogeneous groups, high-ability students dominated discussions, while lower-ability students were more passive and relied on scaffolding from teachers or peers. Furthermore, mathematically rich tasks were more effective in fostering in-depth discussions than non-mathematically rich tasks. These findings highlight the importance of strategic student grouping and scaffolding in promoting engagement and meaningful collective argumentation in mathematics learning.